Medical ethnobotany of herbal practitioners in the Turkestan Range, southwestern Kyrgyzstan - Pawera, L.; Verner, V.; Termote, Céline; Sodombekov, I.; Kandakov, A.; Karabaev, N.; Polesny, Z. (Polish Botanical Society, 2016)
This study recorded and analyzed traditional knowledge of medicinal plants in the Turkestan Range in southwestern Kyrgyzstan, where ethnobotanical knowledge has been largely under-documented to date. Data was collected through participant observation and both semi-structured and in-depth interviews with 10 herbal specialists. A total of 50 medicinal plant taxa were documented, distributed among 46 genera and 27 botanical families. In folk medicine they are applied in 75 different formulations, which cure 63 human and three animal ailments. Quantitative ethnobotanical indices were calculated to analyze traditional knowledge of the informants and to determine the cultural importance of particular medicinal plants. Ziziphora pamiroalaica, Peganum harmala, and Inula orientalis obtained the highest use value (UV). The best-represented and culturally important families were Lamiaceae, Asteraceae, and Apiaceae. Gastro-intestinal system disorders was the most prevalent ailment category. Most medicinal plants were gathered from nearby environments, however, species with a higher cultural value occurred at distant rather than nearby collection sites. The findings of this study proved the gap in documentation of traditional knowledge in Kyrgyzstan, indicating that further studies on the traditional use of wild plant resources could bring important insights into ecosystems’ diversity with implications to human ecology and bio-cultural diversity conservation in Central Asia.